Evaluation of Standard and Proposed Reference Values for Entheseal Thickening by Using Musculoskeletal Ultrasound - Keenan, Marissa; Solmaz, Dilek; Bakirci, Sibel; Roth, Johannes; Eder, Lihi; Aydin, Sibel Zehra (Journal of rheumatology, 2023)
Ultrasound (US) is increasingly used to evaluate enthesitis. One of the US features of enthesitis is thickening. However, there is no consensus on how the entheseal thickening needs to be defined, and existing cut-off levels have been criticized for being frequently positive in healthy controls (HCs). Our objective was to determine the frequency of thickening of entheses on US using the existing cut-off values in HCs and in patients with axial spondyloarthritis (axSpA) and propose new values to improve discriminative value. Eighty HCs and 100 patients with axSpA had US scans of 2160 entheses. Sensitivity, specificity, odds ratio (OR), and accuracy were calculated according to accepted cut-off levels from the literature and proposed cut-offs were calculated as the mean ± 2 SD. Thickening according to current cut-off levels was found in 20.4% (196/960) of healthy participants' entheses and 33% (396/1200) of entheses of patients with axSpA. Thickening according to proposed cut-off levels decreased frequency of thickening in both groups, and therefore increased specificity at the cost of decreasing sensitivity. The only anatomical site where the thickness had a value to discriminate disease from health was seen at the triceps tendon enthesis with an OR of 13.4 (95% CI 4.0-44.8) according to the current cut-offs compared to 10.3 (95% CI 4.0-26.6) with the proposed cut-off levels. Although using cut-offs appears to be an appealing method to evaluate entheseal thickness, the measurements may be affected by several confounding factors, leading to a low discriminative value, except for at the triceps tendon enthesis.